2010
DOI: 10.1016/j.tecto.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonic investigations in the inner Cottian Alps (Italian Western Alps): An integrated approach

Abstract: This work integrates the results of recent geological-structural studies with new seismological data for the inner Cottian Alps to investigate the connection between faults and seismicity. The major post-metamorphic tectonic feature of this sector is represented by a N-S structure, named LisTrana Deformation Zone (LTZ). Since the Late Oligocene this structure accommodated right-lateral (Late Oligocene-Early Miocene) and subsequently normal (post-Early Miocene) displacements. In the Pleistocene, the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…In the analysed area, this extension direction corresponds well with that observed for the second faulting stage and may be related to the present-day activity of N-S normal and/or oblique-normal faults, as proposed by Eva et al (1997) and by Perrone et al (2009b).…”
Section: Correlation With the Adjacent Sectors Of The Northern Cottiasupporting
confidence: 85%
“…In the analysed area, this extension direction corresponds well with that observed for the second faulting stage and may be related to the present-day activity of N-S normal and/or oblique-normal faults, as proposed by Eva et al (1997) and by Perrone et al (2009b).…”
Section: Correlation With the Adjacent Sectors Of The Northern Cottiasupporting
confidence: 85%
“…The Alps-Apennines junction zone, which is subjected to moderate differential uplift, as observed by GPS data (Devoti et al, 2011), is affected by low magnitude instrumental seismicity (M L < 5) despite the fact that historically, earthquakes that have struck this area have reached up to a moderate magnitude (seismic event of the April 2 nd IKM have been compared with the available geological, structural, geomorphological, seismological and GPS data to study the relationship between differential uplift, crustal mobility and the current tectonic activity of this sector. This study contributes to improving the knowledge of the current tectonic activity in the Western Po Plain and provides some new constraints for the recently outlined seismotectonic model (Perrone et al, 2010(Perrone et al, , 2011b …”
Section: Introductionmentioning
confidence: 78%
“…Seismotectonic studies (Perrone et al, 2010(Perrone et al, , 2011a recently showed that the seismic activity of this area could be partly related to the current activity of the N-S regional faults (Col del Lis-Trana Deformation Zone) affecting the inner border of the Cottian Alps, as seismological and structural data show consistent geometry (map view and cross-section) and kinematics (Fig. 4).…”
Section: Seismotectonic Frameworkmentioning
confidence: 88%
See 1 more Smart Citation
“…Lastly, seismic activity that affects the central sector of the Western Alps, with few strong historical earthquakes with a maximum MCS intensity I 0 ¼ VII -VIII (e.g. the 2 April 1808, seismic sequence; Perrone et al, 2010) can be regarded as a probable triggering factor for the rock avalanche.…”
Section: Age Causes and Triggering Factorsmentioning
confidence: 99%